2005
DOI: 10.4141/p04-098
|View full text |Cite
|
Sign up to set email alerts
|

Relationships and inheritance of linolenic acid and seed lipoxygenases in soybean crosses designed to combine these traits

Abstract: Reinprecht, Y., Rajcan, I., Poysa, V. W., Ablett, G. R. and Pauls, K. P. 2005. Relationships and inheritance of linolenic acid and seed lipoxygenases in soybean crosses designed to combine these traits. Can. J. Plant Sci. 85: 593-602. To improve oxidative stability of soybean oil and reduce off-flavours, we previously developed low linolenic acid, lipoxygenase-free (LLA.3lx) soybean germplasm. The objectives of this study were to characterize the patterns of inheritance and determine the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…(1998). However, in a cross between RG10 and a wild‐type line OX948 evidence for minor genes interacting with the major gene was observed (Reinprecht et al. 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(1998). However, in a cross between RG10 and a wild‐type line OX948 evidence for minor genes interacting with the major gene was observed (Reinprecht et al. 2005).…”
mentioning
confidence: 99%
“…OX948 was developed at Agriculture and Agri‐Food Canada, Greenhouse and Processing Crops Research Centre, Harrow, (R. I. Buzzell, unpublished data) as a seed lipoxygenase triple null mutant line (normal linolenic acid). RG10 and OX948 were crossed to produce a recombinant inbred line (RIL) population to map linolenic acid and lipoxygenase genes and to develop novel lines with improved oxidative stability (triple seed lipoxygenase nulls and low linolenic acid levels; Reinprecht et al. 2005, 2006a).…”
mentioning
confidence: 99%
“…It is conceivable that a larger population of LLA.3lx lines would contain some higher yielding lines. It has been demonstrated previously that the LLA and 3lx are independently and simply inherited in the new germplasm (Reinprecht et al 2005) and in a RO mapping study no linkage and correlation between LA, LX and yield were detected (Reinprecht et al unpublished data). Moreover, the current population study showed that the LLA.3lx and HLA.3LX lines were very similar.…”
Section: Discussionmentioning
confidence: 99%
“…The consistently low content of LA (< 30 g kg -1 ) and the absence of seed LX in the LLA.3lx lines tested in different environments (Reinprecht et al 2005) suggests that this novel germplasm may be useful for developing soybean cultivars resistant to oxidative degradation. The 12% lower yield of the six LLA.3lx lines compared with the parental lines may be a real limitation of the unique combination of LLA and 3lx or may reflect the fact that a relatively small number (6) of genotypes with the combined LLA and 3lx traits were tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation